Impact of Promotion techniques on student enrolment in schools - A comprehensive literature review (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The introduction of promotional techniques in schools plays a crucial role in attracting students and increasing enrolment rates. In today's highly competitive educational landscape, schools must employ effective strategies to stand out and appeal to potential students and their families.In the face of heightened competition for student enrollment, institutions are compelled to seek rapid, streamlined, and impactful methods of disseminating information to prospective students during their decision-making journey. In this study, we will explore the different promotional techniques used by different schools to increase their enrolment rate and also the relationship between promotional techniques and student enrolment in schools. This study examines how various strategies can impact the decision-making process of students and their families. School uses different marketing strategies mainly public relation, publicity, advertisement (print and electronic media). This study will help school to use most effective tool to increase their enrolment rate in school. Additionally, this research underscores the significant impact of advertising on bolstering enrollment numbers in schools. Moreover, it highlights a prevailing trend where many school have yet to fully leverage social networks for student recruitment purposes.